35. CLINICAL, SUBCLINICAL FEATURES OF PATIENTS WITH GASTRIC CANCER AT THE DEPARTMENT OF GASTROENTEROLOGY – THONG NHAT HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objectives: Gastric cancer usually has a poor prognosis if being diagnosed at late stages. We evaluate patients with gastric cancer by asking medical history, past history and using subclinical tools such as esophagogastroduodenoscopy, abdominal CT scan and biopsy, therefore performing a diagnosis of early stage gastric cancer.Subjects and Method: Retrospective study, performed in Thong Nhat hospital. Patients who were diagnosed with gastric cancer from Janurary 2023 to February 2024 in our hospital were included in the study. This research evaluates clinical presentation, subclinical presentation as well as pathological presentation of these patients.Results: Of all 73 patients, male accounts for 73%, with an average age of 65,05 ± 10,59. The most common reason of administration of patients with gastric cancer is abdominal pain (84%). Past medical history: Helicobacter pylori infection accounts for 8,1%; family history of GI cancer accounts for 10,8%. The most commonly found site of injury on endoscopy is the incisura angularis (31,1%) and the most common presentation of injuries were ulcers (54,1%). TNM classification of these patients, based on abdominal CT-scan were all IB-staged and above (94,1%). All of our patients had their pathological diagnosis as Adenocarcinomas.Conclusion: The rate of gastric cancer diagnosis at late stages is still high in VietNam. Therefore, evaluation of risk factors as well as clinical symptoms in early stages of gastric cancer is extremely important. This contributes to both screening and treating our patients as early as possible, thus improving their life quality afterwards.
Keywords: Gastric cancer; clinical presentation; endoscopy